2017
DOI: 10.1016/j.paid.2017.04.031
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of emotional intelligence effects on job satisfaction mediated by job resources, and a test of moderators

Abstract: This paper examines whether job resources act as a mediator in the emotional intelligence (EI)-job satisfaction relationship, and examines possible moderators, including gender, age, tenure, and job level. We conducted a meta-analysis to explore these relationships. The metaanalysis demonstrated that: First, EI is positively related to job resources (k = 15, N = 4,151; overall EI: ̂ = .27; ability EI: ̂ = .24; self-report EI: ̂ = .27; mixed EI: ̂ = .28). Second, job resources mediate the relationship between E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 69 publications
8
75
0
Order By: Relevance
“…A substantial body of research has demonstrated that trait EI is essential and important for job-related well being (Zampetakis and Moustakis, 2010;Fu, 2014;Schutte and Loi, 2014;Petrides et al, 2016;Clarke and Mahadi, 2017;Sun et al, 2017). Moreover, a meta-analysis study revealed that EI was positively correlated with job satisfaction (Miao et al, 2016(Miao et al, , 2017. Prior studies have demonstrated that the positive influence of EI on job satisfaction is well proven; however, the deeper mechanism of this association is unclear.…”
Section: Trait Emotional Intelligence and Job Satisfactionmentioning
confidence: 99%
“…A substantial body of research has demonstrated that trait EI is essential and important for job-related well being (Zampetakis and Moustakis, 2010;Fu, 2014;Schutte and Loi, 2014;Petrides et al, 2016;Clarke and Mahadi, 2017;Sun et al, 2017). Moreover, a meta-analysis study revealed that EI was positively correlated with job satisfaction (Miao et al, 2016(Miao et al, , 2017. Prior studies have demonstrated that the positive influence of EI on job satisfaction is well proven; however, the deeper mechanism of this association is unclear.…”
Section: Trait Emotional Intelligence and Job Satisfactionmentioning
confidence: 99%
“…Schneider, Lyons and Khazon (2013) found that individuals who scored high in ability-based EI measures reported lower threat appraisals, negative emotions, and physiological stress responses over time in relation to cognitive and social stress. Research also suggests that EI training helps people manage workplace stress better, since several researchers argue that emotional intelligence is a skill that correlates with positive outcomes for workers dealing with stress (Duncan et al, 2013;Eack et al, 2010;Martins, Ramalho & Morin, 2010;Miao, Humphrey & Qian, 2017;Zeidner, Hadar, Matthews & Roberts, 2013;Zeidner & Matthews, 2016;Zeidner, Matthews, & Roberts, 2012). Ashkanasy and Dorris (2017) and Cotê (2014) argue that EI improves workers' perceptions of and emotional responses to work stress.…”
Section: Thesis Focus and Motivationmentioning
confidence: 99%
“…Researchers, business practitioners, and pop psychology authors continue to debate the terms of EI-how it should be defined, operationalised, and measured-and what predictive and incremental properties it possesses beyond extant personality and intelligence measures Côté, 2014Daus & Ashkanasy, 2003Matthews, Zeidner, & Roberts, 2007;Mayer, Caruso, & Salovey, 2016;Mayer, Roberts, & Barsade, 2008;Mayer, Salovey, & Caruso, 2008;Zeidner, Matthews & Roberts, 2012;Zeidner, Roberts, & Matthews, 2004). Despite disparate conceptualisations of EI, a meta-analysis from Miao, Humphrey, & Qian (2017) suggested that consensus has been reached; EI can be categorised into three conceptual streams, differentiated by theory and method . Stream 1 is based on the ability model developed by Mayer and Salovey (1997), which categorises EI into four kinds of abilities: a) perceiving emotion in oneself and others, b) integrating emotion to facilitate thought, c) understanding emotion in oneself and others, and d) regulating and managing emotions.…”
Section: Emotional Intelligence History and Conceptsmentioning
confidence: 99%
See 2 more Smart Citations